EFEKTIVITAS PENGGUNAAN APLIKASI PEMBELAJARAN DARING PADA MATA PELAJARAN SIMULASI DAN KOMUNIKASI DIGITAL SMK NEGERI 2 PINRANG - Andi Satriani; Syahrul; Riana T. Mangesa (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
This study aims to discover: (1) the effectiveness of using online learning applications, (2) students’ learning activities on the use of online learning applications, and (3) students’ responses on the use of online learning applications. The type of research employed pre-experimental. The population of the study were students of grade X Computer Engineering and Network at SMKN 2 Pinrang. The sample of the study was the students of grade X TKJ2 with the total of 36 students who were determined using the Cluster Random Sampling technique. The research data was obtained by using tests, observations, and questionnaires. The results of the study reveal that the learning outcomes after using online learning applications have increased as well as their activities. The results of students’ responses on the use of online learning applications received a positive response. Based on the research, it is concluded that the use of online learning applications is effective in improving learning outcomes and activities during the learning process.